Meningkatkan Literasi Tulis Siswa dengan Media KB Sebagai Upaya Mendukung Gerakan Literasi Sekolah - Albuni, Hepni (Jurnal Didaktika Pendidikan Dasar, 2022)
The average ability of class VII B students in writing literacy is still low, especially in stringing sentences into paragraphs. The low ability can be seen from the daily test results of students who get a score of 70 as much as 45%. Whereas in the KKM it is stated that students are said to be complete if they meet a minimum score of 70 as much as 70%. This study aims to improve written literacy and student learning outcomes. The method chosen in this study is a qualitative descriptive method using literacy-based learning media in the form of pictorial cubes with the following strategies and completion steps: the teacher divides students into several groups, students share tasks in their groups, students arrange one one by one sequence of images and write down the results, The final activity is to present the results in front of the class. Data was collected by means of tests and observations of 22 class VII B students. The results showed that family planning media could improve written literacy and student learning outcomes. Completeness of student learning before using family planning media reached 54, 54% to 77.28%. Based on the results of this study, it can be concluded that family planning media can improve writing literacy.